Performance Evaluation Models for School Principals: Insights from Supervisory Practices in Yogyakarta, Indonesia - Ernani Astuti; Lia Yuliana; Muh. Saidil Ikhwan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective principal performance assessment plays a vital role in enhancing school leadership, teacher effectiveness, and student outcomes. However, the implementation of such evaluations often faces various practical challenges. This study investigates the principal assessment process at SMA Pangudi Luhur Yogyakarta, aiming to identify key obstacles and propose actionable improvements. A qualitative research design was employed, incorporating in-depth interviews with principals, vice principals, and school supervisors, as well as document analysis. The data were thematically analyzed to uncover recurring issues and patterns in the assessment process. The findings reveal three primary challenges: (1) limited understanding of assessment criteria and components among vice principals, (2) insufficient technical support provided by school supervisors, and (3) lack of structured mentoring during the verification stage. These issues hinder the reliability and effectiveness of the principal evaluation process. To improve the assessment system, the study recommends targeted technical training for school staff, integration of digital tools for efficient data management, and strengthened collaboration among stakeholders involved in the evaluation process. These strategies are expected to enhance the transparency, accuracy, and impact of principal performance assessments. This study contributes to the discourse on educational leadership by identifying critical gaps in current assessment practices and offering practical solutions. Although limited to a single institution, the findings provide a foundation for broader investigations into principal evaluations across different school contexts and their long-term effects on school improvement.